2020
DOI: 10.1039/d0na00141d
|View full text |Cite
|
Sign up to set email alerts
|

A WS2-gold nanoparticle heterostructure-based novel SERS platform for the rapid identification of antibiotic-resistant pathogens

Abstract: The emergence of antibiotic-resistant bacteria is the biggest threat to our society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
(185 reference statements)
0
19
0
Order By: Relevance
“…Interestingly, in the latter case, there was a ∼10-fold enhancement in the intensity of the A 1g mode of WS 2 QDs owing to the surface-enhanced Raman spectroscopy (SERS) effect caused by the Au NPs. Au NPs are well-known SERS materials that enhance the Raman signal via electromagnetic field enhancement . The Raman spectra for both the cases were deconvoluted, and a stacked plot is displayed in Figure b.…”
Section: Results and Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, in the latter case, there was a ∼10-fold enhancement in the intensity of the A 1g mode of WS 2 QDs owing to the surface-enhanced Raman spectroscopy (SERS) effect caused by the Au NPs. Au NPs are well-known SERS materials that enhance the Raman signal via electromagnetic field enhancement . The Raman spectra for both the cases were deconvoluted, and a stacked plot is displayed in Figure b.…”
Section: Results and Discussionmentioning
confidence: 83%
“…In addition to manipulating optical properties, metal nanostructures are also used as efficient surface-enhanced Raman scattering (SERS) substrates. Pramanik et al reported a study on the integration of Au nanoparticles (NPs) with WS 2 nanosheets as a novel SERS platform for detecting antibiotic-resistant bacteria . To the best of our knowledge, the effect of Au NPs on the optical properties of WS 2 QDs is not yet explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of cheaper, highly conductive 2D dimensional nanomaterials, such as graphene and molybdenum disulfide, interest in the sensing applications of mature nanomaterials like CNT and nanoAg has begun to wane. Recent work [ 87 ] employing a 2D–0D heterostructure-based SERS platform in the rapid detection of Salmonella DT104 utilized an alternative transduction element consisting of a (2D) WS2 transition metal dichalcogenide (TMD) and a (0D) plasmonic gold nanoparticulate (GNPs) lattice. The authors showed the device could rapidly discriminate multidrug resistant Salmonella DT104 from S. Typhi using AST and Augmentin antibiotics up to concentrations of 100 CFU/mL.…”
Section: Emerging Biosensorsmentioning
confidence: 99%
“…An SEM image showing the damaged walls of Salmonella Typhi ( d ) after treatment with the Augmentin antibiotic. Figure modified with permission from [ 87 ]. (Copyright 2020, American Chemical Society).…”
Section: Figurementioning
confidence: 99%